Draft genomes of two phylotype I and II Ralstonia solanacearum species complex (RSSC) isolates causing bacterial wilt in tomato plants from Costa Rica - Galiano Murillo, Fiorella (2024)
Bacteria from RSSC hold agricultural significance as they are the causal agents of bacterial wilt. Here, we report the draft genomes of two bacteria extracted from vascular tissues of infected tomato plants. Isolate RALF-MA was classified as Ralstonia pseudosolanacearum (phylotype I) and RALSA-MA as Ralstonia solanacearum (phylotype II).